2022
DOI: 10.3847/1538-4357/ac8cfa
|View full text |Cite
|
Sign up to set email alerts
|

First Laboratory Measurement of Magnetic-field-induced Transition Effect in Fe x at Different Magnetic Fields

Abstract: The magnetic field is extremely important for understanding the properties of the solar corona. However, there are still difficulties in the direct measurement of the coronal magnetic field. The magnetic-field-induced transition (MIT) in Fe x, appearing in coronal spectra, was discovered to have prospective applications in coronal magnetic field measurements. In this work, we obtained the extreme ultraviolet spectra of Fe x in the wavelength range of 174–267 Å in the Shanghai High-temperature Superconducting E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 51 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…The effect of the MIT in Fe X at different magnetic fields has been verified experimentally in the laboratory by Xu et al (2022).…”
Section: Laboratory Measurementmentioning
confidence: 89%
See 3 more Smart Citations
“…The effect of the MIT in Fe X at different magnetic fields has been verified experimentally in the laboratory by Xu et al (2022).…”
Section: Laboratory Measurementmentioning
confidence: 89%
“…They obtained a value of 3.5 cm −1 with an upper limit of 7.8 cm −1 . A similar method was employed by Xu et al (2022) and they determined ΔE = 8.6 ± 2.7 cm −1 , which is, however, much larger than that from Li et al (2016). The authors discussed the uncertainties from atomic data, spectrometer efficiency calibration and data statistics.…”
Section: δEmentioning
confidence: 96%
See 2 more Smart Citations
“…Recently, Li et al (2015Li et al ( , 2016 noticed the magnetic-field-induced transition (MIT) in the Fe ion and suggested that it can be used to diagnose coronal magnetic field strength (also see Li et al 2021;Xu et al 2022). Si et al (2020) developed the direct line ratio technique and applied this method to spectral observations taken by EUV Imaging Spectrometer (EIS, Culhane et al 2007) onboard Hinode, and the suitability of the method has been validated through forward modeling with a series of MHD models (Chen et al 2021a(Chen et al ,b, 2023Liu et al 2022;Martínez-Sykora et al 2022).…”
Section: Introductionmentioning
confidence: 99%